Effect of relative humidity and sea level pressure on electrical conductivity of air over Indian ocean - Pawar, S. D.; Murugavel, P.; Lal, D. M. (Journal of Geophysical Research-Atmospheres, 2009)
The electrical conductivity measured over the Indian Ocean (15 degrees N, 77 degrees E to 20 degrees S, 58 degrees E) during the Indian Ocean Experiment (INDOEX-1999) from 20 January to 12 March 1999 has been analyzed. The conductivity values over two oceanic regions, one with very low aerosol concentration and another with very high aerosol concentration, are studied in relation with meteorological parameters such as relative humidity and sea level pressure. The average conductivity is as low as 0.295 x 10(-14) Sm-1 in the region of high aerosol concentration and it is 0.783 x 10(-14) Sm-1 in the region of very low aerosol concentration. In both the regions, conductivity shows an inverse relation with relative humidity and this effect is more in the presence of high aerosol concentration. The hydrate growth of aerosol particles in high-humidity condition may be responsible for the inverse relation between conductivity and relative humidity. Size distributions of aerosol particles measured in the same cruise during high-humid conditions are also analyzed to show that sizes, rather than numbers, of aerosol particles increase with an increase in humidity. The relationship between conductivity and sea level pressure in these two regions is also studied and it shows good correlation in the region where the background aerosol concentration is low and no correlation in the region where aerosol concentration is high. The inverse relation between sea level pressure and electrical conductivity is attributed to the possible transportation of ultrafine particles from free troposphere, with subsiding motions associated with high pressure. The positive correlation between ultrafine particles and sea level pressure supports this idea.